2009
DOI: 10.1080/02699200802491165
|View full text |Cite
|
Sign up to set email alerts
|

Using conversation analysis to explore the recurrence of a topic in the talk of a boy with an autism spectrum disorder

Abstract: Some higher functioning individuals with autism spectrum disorders (ASDs) are reported to produce perseverative talk, especially around 'special interests'. Topic perseveration is a form of pragmatic impairment captured in Prizant and Rydell's (1993) continuum of unconventional verbal behaviour in autism. Although widely reported, there is little systematic empirical research into this phenomenon. This paper considers the utility of Conversation Analysis in developing knowledge in this area, drawing upon data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 32 publications
0
25
1
Order By: Relevance
“…Nevertheless, the qualitative analysis of the videos revealed that the children's joint attention increased over the sessions. These results are contradictory with other studies, which refer that, the use of robots could elicit repetitive motor behaviours (Lund et al, 2009;Stribling et al, 2009).…”
Section: Discussioncontrasting
confidence: 56%
“…Nevertheless, the qualitative analysis of the videos revealed that the children's joint attention increased over the sessions. These results are contradictory with other studies, which refer that, the use of robots could elicit repetitive motor behaviours (Lund et al, 2009;Stribling et al, 2009).…”
Section: Discussioncontrasting
confidence: 56%
“…Speakers with ASD, however, may not be attuned to the face-work negotiations just described. A lack of attunement may partially explain tendencies to pursue or repeat topics of interest even when conversation partners appear unengaged (Stribling et al, 2009). …”
Section: Face-work and The Pursuit Of Responsementioning
confidence: 98%
“…We investigate both the conditions under which this form of repetition is produced, and the interactional consequences of repetition in a peer group context. CA work on echolalia Stribling, Rae, & Dickerson, 2007) and topic perseveration (Dobbinson, Perkins, & Boucher, 2003;Stribling, Rae, & Dickerson, 2009) has re-examined repetition by speakers with ASD, which was once categorized as a target for remediation. Conceptualizations have now shifted from viewing repetition as an exclusively within-child marker of linguistic deficit that hinders interaction, to a more interactionally structured phenomenon that is responsive to surrounding talk and is conversationally relevant.…”
mentioning
confidence: 98%
“…While issues of repetition in language have been addressed by psycholinguistics, especially in relation to alzheimer's disease (Schneck et al 1982;Katzman 1985;Swihart and Pizzolo 1988) and autism (Stribling et al 2009;Sterponi and Shankey 2013), and while sociolinguistics has addressed this as well (hamilton 1994;Ramanathan 1997;Davis 2005;Schrauf and Iris 2012), the role of repetition in PtSD from a critical psycho-and sociolinguistic orientation is underresearched. This paper bridges this gap.…”
Section: Introductionmentioning
confidence: 99%